2007
DOI: 10.1002/ange.200701565
|View full text |Cite
|
Sign up to set email alerts
|

Tandem‐Aktivierung von Si‐C‐ und C‐H‐Bindungen bei Decamethylhafnocen und Bis(trimethylsilyl)acetylen

Abstract: Hafnium triumphiert über Titan und Zirconium! Ungewöhnliche Si‐C‐ und C‐H‐Aktivierungen durch Hafnium zum Alkenylkomplex 2 und Silahafnacyclopenten 3 wurden in der Reaktion von Decamethylhafnocen und Bis(trimethylsilyl)acetylen beobachtet. Die höhere Reaktivität von Hafnocenverbindungen gegenüber den Titanocen‐ und Zirconocen‐Analoga ist von genereller Bedeutung für Synthesen, Reaktionen und katalytische Anwendungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In this context, it should be noted that unexpected, yet significant changes in reactivity were observed before when going from zirconocenes to hafnocenes. Examples include C À H and Si À C bond activations in the synthesis of decamethylhafnocene alkyne complexes, [30] THF ring-opening reactions [31] as well as more recently dinitrogen activation and functionalization at Group 4 metallocenes. [32] DFT study of the metallacycles 3 M: To get a more detailed picture of the bonding situation in the complexes 3 M, DFT calculations on the BVP86/A C H T U N G T R E N N U N G (6-311+GA C H T U N G T R E N N U N G (d,p)/LANL2DZ) level of theory were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it should be noted that unexpected, yet significant changes in reactivity were observed before when going from zirconocenes to hafnocenes. Examples include C À H and Si À C bond activations in the synthesis of decamethylhafnocene alkyne complexes, [30] THF ring-opening reactions [31] as well as more recently dinitrogen activation and functionalization at Group 4 metallocenes. [32] DFT study of the metallacycles 3 M: To get a more detailed picture of the bonding situation in the complexes 3 M, DFT calculations on the BVP86/A C H T U N G T R E N N U N G (6-311+GA C H T U N G T R E N N U N G (d,p)/LANL2DZ) level of theory were performed.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it should be noted that unexpected, yet significant changes in reactivity were observed before when going from zirconocenes to hafnocenes. Examples include CH and SiC bond activations in the synthesis of decamethylhafnocene alkyne complexes,30 THF ring‐opening reactions31 as well as more recently dinitrogen activation and functionalization at Group 4 metallocenes 32…”
Section: Resultsmentioning
confidence: 99%
“…While most of the bis(trimethylsilyl)acetylene group 4 metallocene chemistry was described for titanium and zirconium, recently the field was extended also to hafnium complexes . In this connection an exciting Si−C activation process has been found that points to some differences in the chemical behavior of zirconium and hafnium …”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by this study and the above-mentioned interaction of zirconocene with the Si−H moiety attached to an alkyne as well as by the recent example of hafnium Si−C activation we decided to extend our research to the chemistry of group 4 metallocene complexes of oligosilylalkynes.…”
Section: Introductionmentioning
confidence: 99%
“…[8] According to the authors its formation proceeds via oxidative addition of the hafnocene fragment across the Si À C bond and subsequent rearrangement to the vinylidene complex, which stabilizes itself by oxidative addition into a methyl group of a Cp* ligand. Similar reaction patterns have been observed in the chemistry of Chiriks dinitrogen complexes.…”
mentioning
confidence: 99%